Analisis Efektivitas Standar Operasional Prosedur (SOP) Terhadap Kinerja Karyawan Bagian Logistik Dan Distribusi Di CV. Sinar Teknik Perkasa - Muhammad Fais Rahman Hakim; Viandra Rahayuna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the effectiveness of Standard Operating Procedures (SOP) on the performance of employees in the logistics and distribution department at CV. Sinar Teknik Perkasa. The research method used is descriptive qualitative. The subject of this research is CV. Sinar Teknik Perkasa, located at Central Dawuan, Cikampek, Karawang, West Java 41373. Data collection techniques used were interviews and observation. The results of the interviews and observations were analyzed by data reduction, data presentation, and drawing conclusions. The preliminary study results show that the implementation of SOP in the logistics and distribution department at CV. Sinar Teknik Perkasa has been effective. The preparation of SOPs was carried out by making field notes on mentoring activities and compiling SOP formats. Meanwhile, the implementation of SOP preparation assistance was carried out in six stages, namely the preparation stage, the formation of an implementation team, planning, drafting, testing SOP drafts, and implementing SOPs. SOPs are needed to regulate the quality assurance of organizational management.